Kawasaki disease complicated by peripheral gangrene and a ventricular septal defect: An unusual association - Mohsin, Muhammad; Akhtar, Saleem (The Turkish Journal of Pediatrics, 2019)
Kawasaki disease is an acute febrile illness associated with the vasculitis of small and medium size arteries. Peripheral gangrene is very rare but a known complication of Kawasaki disease mostly reported in the infantile age group. Early therapy is advocated for prevention of serious complications. We report a 10-month-old girl with Kawasaki disease and a small ventricular septal defect who developed peripheral gangrene despite initiation of early therapy.
Keywords: Kawasaki disease; complications; infant; peripheral gangrene